The Correlation Between Self-Efficacy and Learning Motivation in 11th Grade of Senior High School: Hubungan Antara Efikasi Diri dengan Motivasi Belajar pada Siswa Kelas XI Sekolah Menengah Atas - Larasati Suryaning Rahayu; Ririn Dewanti Dian (Universitas Muhammadiyah Sidoarjo, 2022)
This study investigates the correlation between self-efficacy and learning motivation among 11th grade students at SMA Trimurti Surabaya, Indonesia. With the disruption caused by the COVID-19 pandemic, online learning has been implemented to mitigate the spread. A sample of 86 students from a population of 110 was selected for this quantitative research, using Likert-scale self-efficacy and learning motivation scales for data collection. The analysis revealed a positive correlation between self-efficacy and learning motivation (rxy=0.334, p<0.05). The coefficient determination showed that self-efficacy accounts for 11.1% of the variation in learning motivation, while other factors contribute to the remaining 88.9%. These findings imply that students with higher self-efficacy tend to exhibit higher learning motivation. The study highlights the significance of self-efficacy as a potential factor to consider when promoting student motivation in online learning environments, particularly during the COVID-19 pandemic. Highlights: The study examines the correlation between self-efficacy and learning motivation among 11th grade students in the context of online learning during the COVID-19 pandemic. A sample of 86 students from SMA Trimurti Surabaya was used to gather quantitative data using Likert-scale self-efficacy and learning motivation scales. The findings indicate a positive correlation between self-efficacy and learning motivation, suggesting that students with higher self-efficacy exhibit higher levels of motivation in their online learning endeavors. Keywords: self-efficacy, learning motivation, 11th grade students, online learning, correlational study